2020
DOI: 10.1055/a-1194-5104
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Ocular Trauma Score and Pediatric Ocular Trauma Score as Two Prognostic Models in Pediatric Open Globe Injuries

Abstract: Aim To compare the ocular trauma score (OTS) and the pediatric ocular trauma score (POTS) as prognostic models of visual outcome after open globe injury in children during a period of 19 years. Patients and Methods A retrospective study of 36 open globe injuries in 36 patients younger than 18 years was conducted from January 2000 to January 2019. For each case, OTS and POTS points were calculated. Results Significant differences were observed in our patients using the two models regarding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In their study, Awidi et al [ 16 ] concluded that POTS correlated better with the final VA in the pediatric population than OTS. However, our results were in coherence with a recent study by Pahor D et al [ 17 ], which concluded that OTS is a better predictor of visual prognosis in ocular trauma patients while POTS grossly underestimated the visual potential.…”
Section: Discussionsupporting
confidence: 92%
“…In their study, Awidi et al [ 16 ] concluded that POTS correlated better with the final VA in the pediatric population than OTS. However, our results were in coherence with a recent study by Pahor D et al [ 17 ], which concluded that OTS is a better predictor of visual prognosis in ocular trauma patients while POTS grossly underestimated the visual potential.…”
Section: Discussionsupporting
confidence: 92%
“…When the epidemiological data in this study were evaluated, was found that most of the children who were admitted to the hospital due to ocular trauma were male. This finding is consistent with many case series in the literature 9,10 . The main reason for this is that boys are more active than girls and are less cautious in dangerous situations.…”
Section: Discussionsupporting
confidence: 91%
“…The success of both trauma scoring systems in predicting visual outcome was evaluated comparatively in different studies, and conflicting results were obtained. Two different studies conducted by Pahor et al 9 and Morgan et al 10 suggested that the success of both scoring systems in predicting visual outcome was similar and POTS did not have any additional contribution. However, different studies conducted by Awidi et al 3 and Shah et al 11 reported that the success of POTS in predicting visual outcome was better than OTS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Among them, 35 patients were <18 years old (70%) and 15 patients were >18 years old (30%). Similar numbers of cases were included in studies conducted by Morgan et al, Kasahara et al, Pahor et al to compare ocular trauma score and pediatric ocular trauma score [11,12] . Out of the 50 patients, 20 were categorized under POTS due to penetrating ocular injury.…”
Section: Discussionmentioning
confidence: 99%